Studies in Contemporary Jewry. - Mendelsohn, Ezra (Oxford University Press, 1999)
Like others in the series, this book presents current scholarship in the form of a symposium, essays, and book reviews by distinguished experts in Jewish studies from around the world. It is published annually by the Avraham Harman Institute of Contemporary Jewry at The Hebrew University of Jerusalem.